Effect of Rootstock Cultivar, Pruning Method and Crop Load on Botrytis cinerea Rot of Vitis vinifera cv. Chenin blanc grapes - Ferreira, J.H.S.; Marais, P.G. (South African Journal of Enology and Viticulture, 2017)
The effect of five rootstock cultivars and two pruning methods with two crop loads each on Botrytis cinerea Pers. rot of Vi tis vinifera L. cv. Chenin blanc was investigated. The effect of these factors on bunch compactness, berry skin strength, pedicel strength, total soluble solids and nitrogen content of berries was also investigated to determine the correlation between these parameters and botrytis rot. The most rot occurred with Chenin blanc on Ramsey, 110 Richter and 101-14 Mgt when spur pruned, while the least rot occurred with Chenin blanc on 99 Richter when cane pruned. Rootstock cultivar had a significant effect on bunch compactness, berry skin strength, pedicel strength, cane mass and crop mass while rootstock cultivar and pruning method had a significant effect on total nitrogen and total soluble solids of berries. Except for bunch compactness none of the other parameters appear to have any direct effect on botrytis rot.